Restitution - YEO, Tiong Min (Institutional Knowledge at Singapore Management University, 2010)
The most significant case in the law of restitution in 2009 is probably Skandinaviska Enskilda Banken AB (Publ), Singapore Branch v Asia Pacific Breweries (Singapore) Pte Ltd [2009] 4 SLR(R) 788 (Belinda Ang Saw Ean J), which involved many points in the law of restitution, although the central points in the case turned on agency law. In addition, there were a number of decisions on various aspects of the law of restitution, sometimes touching on the subject only incidentally.